Characterization and evaluation of antioxidant potential of onion peel extract of eight differentially pigmented short-day onion (Allium cepa L.) varieties - Gorrepati, Kalyani; Kumar, Ashok; Ahammed Shabeer, T. P.; Khan, Zareen; Satpute, Prashant; Anandhan, Sivalingam; Arunachalam, Thangasamy; Yalamalle, Vishwanath Rohidas; Mahajan, Vijay; Singh, Major (Frontiers in Sustainable Food Systems, 2024)
Outer papery peel of onion bulb is an inevitable bio-waste generated in the course of postharvest handling and processing. Onion peels are rich source of nutraceutically important polyphenolic compounds having many therapeutic potentials. Here, we characterized onion peel extract (OPE) of eight differentially pigmented short-day onion varieties through ultrahigh-performance liquid chromatography coupled with high resolution single stage Orbitrap spectrometry and evaluated the antioxidant potential. Total 49 phenolic compounds were identified in this study which includes 33 anthocyanin, 08 flavanol, 04 flavones and one each of pyranoanthocyanin, chalcone, phenolic acid, and ellagiotannins. Anthocyanin was the most abundant polyphenolic compound followed by flavanol in all the varieties. Among anthocyanin, 10 cyanidin, 10 delphinidin, 4 peonidin, 4 petunidin, 3 pelargonidin, and 2 malvidin were identified. Cyanidin-3-(6-malonylglucoside), delphinidin and delphinidin-3galactoside were the predominant pigment in dark red varieties (BDR and BRJ) and its abundance suggests a key role in the differential pigmentation pattern of onion peel. Total phenol content (TPC) in peels ranged 1738.21-1757.76 mg GAE/100g DW in dark red onion, 1306.58-1646.73 mg GAE/100g DW in red onion, and 78.77-85.5 mg GAE/100g DW in white onion varieties. The mean total anthocyanin content was maximum (28.23 mg/100g DW) in dark red varieties (BDR) and minimum (0.11 mg/100g DW) in white variety (BSW).Total antioxidant activity was ranged 4.71-79.80 µmol/g DW, 22.71-286.7 µmol/g DW and 8.72-156.89 µmol/g DW estimated through FRAP, ABTS, and DPPH methods respectively. In all three methods, it was maximum in dark red var. BDR and minimum in white var. BSU.